Diseño de una Ruta Aviturística en el cantón Saquisilí, provincia de Cotopaxi. - Campaña Quisaguano, Jhonny Danilo (2022)
The design of the Birdwatching Route of the Saquisilí Canton, province of Cotopaxi, allows generating an analysis of data and primary and secondary information of the study area, in order to promote tourist activity within the area and therefore the socioeconomic situation of its population. Within the situational diagnosis of the Saquisilí canton, it is distinguished that being a canton located in the Andean region has a type of cold temperate climate particular to the desert area of the Andes, where there are four areas for gathering information, where the climatic, geographic and access conditions to house and observe various species of birds are ideal, because they inhabit within the altitude range and the geographic area planned for this project. Therefore, the evaluation and identification of ornithological species through field trips with the purpose of determining and recording the species that were observed and recognized, through observation methods, with intensive search being the one that best fit this study, and the GPS, for the collection and validation of data that served to corroborate the inventory of birds carried out in the canton, which has 19 species, 5 orders and 13 families, where the order Passeriformes stood out before the rest of the bird species of the canton with 8 families including Furnnariidae, Fringillidae, Emberizidae, Turdidae and Cinclodes execelsio, the birds that stand out in this inventory are: Chingolo, Huirachuros, Chiguanco Blackbird, Giant Hummingbird, Long-Eared Turtle Dove, Witch Bird, Andean Reddish Duck, Yellow-billed Duck, Yellow-footed Duck minor, Vanellus resplendens. All the birds registered in the bird inventory of the Saquisilí canton are categorized in a conservation status of minor concern (LC), this due to the endemism of the species, since the vast majority of the birds are native to the area, and where a key point of agglomeration and bird watching has been the natural attraction Cascada Candela Faso. Once the information has been systematized, through the orientation of the route design and the union of the proposed itinerary, the result is a Birdwatching Route in the Saquisilí canton with a total route of 65 km through the four areas described above, with a duration of two days. , through an altitude that varies between 2,862 meters above sea level to 3,949 meters above sea level due to a paramo climate, with a first-order road accessibility in the urban section and a second-order road in the rural section that is currently in good condition, it has 3 hotels for lodging, 3 cooperatives of mixed vans and 1 of taxis, as well as 6 restaurants for food. Being these key factors for a good development within the Birdwatching Route in the Saquisilí canton.